(untitled) (Scientific journal of the Fergana State University, 2024)
As a result of adaptation of the digestive organs to substances found in the intestinal cavity, the morphological structure and functional state of the gastrointestinal system changes sharply from its initial section to its final section. The initial and middle sections of the intestine play an important role in the hydrolysis and absorption of proteins, fats and carbohydrates. The functional activity of the last section of the intestine is low and it serves as a secret source. When the functional activity of the gastrointestinal system decreases for some reason, the enzymes of the last section of the intestine are activated and perform a compensatory function.